Implementasi Kebijakan Peraturan Gubernur Nomor 77 Tahun 2020 Tentang Pengelolaan Sampah Di Lingkup Rukun Warga (Studi Kasus Bank Sampah Mawar Putih Rt 009 Rw 002 Kelurahan Tugu Selatan Kecamatan Koja Jakarta Utara) - Alwasury, Arditta; Maesarini, Indah Wahyu (Jurnal Ilmu Administrasi Publik, 2024)
This research is based on the Primary Tasks and Functions of Waste Management at the neighborhood level in South Tugu Village, Koja District, North Jakarta, referring to Governor Regulation No. 77 of 2020 concerning the establishment of management facilities and infrastructure at the neighborhood level in North Jakarta. This includes managing waste at the neighborhood level and educating the community on proper Waste Management. Various issues related to Facilities and Infrastructure, Budget, and Human Resources were identified. The purpose of this study is to understand and analyze the implementation of Governor Regulation No. 77 of 2020 on Waste Management at the neighborhood level in South Tugu Village, Koja District, North Jakarta. The Waste Bank is a concept that collects dry household waste (Plastic, Paper, Cans, etc.) and converts it into cash through a system that encourages residents to participate in waste sorting and recycling. Daily household waste production is a fundamental problem. According to the Ministry of Environment and Forestry, household waste accounted for 45.9% of Indonesia's total waste production in 2021, which reached 41.38 million tons, with  26.96 million tons of that total estimated to be improperly managed. This study employs a qualitative method aimed at creating a systematic and accurate description of the facts and the relationships among the phenomena investigated by the author. The research results indicate four key indicators: Communication, Resources, Disposition, and Bureaucratic Structure. To ensure the effective implementation of Governor Regulation No. 77 of 2020 on waste management, it is necessary to create a fixed budget for facilities and infrastructure by identifying and recording the detailed needs and proposals for the required facilities and infrastructure.